Impact of dronedarone on the risk of myocardial infarction and stroke in atrial fibrillation patients followed in general practices in Germany. (1st March 2019) - Ehrlich, Joachim R.; Look, Christiane; Kostev, Karel; Israel, Carsten W.; Goette, Andreas
Abstract: Background: The goal of this study was to analyze the impact of dronedarone on the risk of myocardial infarction and stroke in atrial fibrillation (AF) patients followed in general practices in Germany. Methods: This study included patients who had received a first prescription of dronedarone, amiodarone, flecainide, propafenone, or sotalol in 1258 general and 62 cardiology practices between January 2010 and March 2017 (index date). The main outcomes of this study were the percentages of patients with myocardial infarction and stroke in the dronedarone group and in the group of individuals who had received other antiarrhythmic drugs within six years of the index date. Cox proportional regression models were used to estimate the relationship between dronedarone and myocardial infarction and stroke. Results: This study included 3498 individuals who had received dronedarone and 17, 724 individuals who had received other antiarrhythmic drugs. After six years of follow-up, 3.9% of patients who had received dronedarone and 5.2% of patients who had received other antiarrhythmic drugs had been diagnosed with myocardial infarction (log-rank p -value = 0.002). At the end of the follow-up period, 7.4% of individuals with dronedarone prescriptions and 8.3% of those who had been prescribed other antiarrhythmic drugs had been diagnosed with a stroke (log-rank p -value = 0.003). Dronedarone was associated with a significant decrease in the risk of developing myocardial infarction (HR = 0.78) and suffering a stroke (HR = 0.84) compared to other antiarrhythmics. Conclusions: In our study, dronedarone was associated with a lower risk of myocardial infarction and stroke in patients with AF compared to other antiarrhythmics. Highlights: This study included 21, 222 patients receiving antiarrhythmic drugs. Dronedarone was associated with a lower myocardial infarction risk compared to other antiarrhythmics. Dronedarone was associated with a lower stroke risk compared to other antiarrhythmics.